Awareness and Knowledge of Libyan Women about Endometriosis - Eljamay, Salwa Muftah; ELHASSADI , JANNAT EBRAYEK (Data Sciences Indonesia (DSI), 2023)
Endometriosis is a long-lasting state in which endometrial-like tissue is found outside the uterus often on the reproductive organs, bowel, and bladder. Aimed to: To find out the extent to which Libyan women know about endometriosis. Martial & Methods: During the one-year study period [2021 to 2022], answer the questions of questionnaire and interview. Result: Most of the ages were between (16 - 25 Years) 1353(73.5 %), most Education Levels (University) 1357(73.8 %), and Marital Situation the most were (Single) 1467(79.7 %). frequency and percent of Knowledge Questions Most of the answers were “I don’t know” and the answer was “No.” This indicates a lack of information about endometriosis, who suffer from endometrioses were the highest percent 75.5 %, I Don`t know 21.2 %. Percent of education the answer I don`t know 19.4 %, and by no 26.1 %. The Correlations between Knowledge and Education Levels, the p-value > 0.05 means there is no relationship between education level and knowledge of endometriosis. Conclusion: that the educational level has nothing to do with the extent of awareness among women about endometriosis, and therefore we find that the percentage of those suffering from endometriosis is very high, and that women need a lot of awareness and knowledge about the endometriosis disease.